Theory and Application of Regional Head Transactional Leadership - Rifdan Rifdan; Mizan Abdul Wahid Yabuno; Risma Niswaty (Universitas Negeri Makassar, 2022)
A leader is an absolute person, always and must exist in an organization or an institution. In his leadership, a leader certainly has its own character to move its personnel or members. To realize proper and quality organizational performance, it is necessary to have adequate leadership. The leadership must be able to motivate or encourage its staff by inspiring or inspiring their creativity in their work. One of the types of leadership is transactional leadership. The organization will be able to achieve its goals if there is a synergy between leaders and subordinates who have a shared commitment to build and develop the organization. However, these ideal conditions are not easy to be realized in organizations. Some subordinates are not able to show good work performance so that it becomes a burden for leaders and organizations including in public organizations. To overcome this situation, the leader takes anticipatory steps to subordinates to spur the performance of subordinates so that they become better. At least transactional leadership can still be applied by giving rewards and punishments to bureaucratic apparatus so that bureaucratic officials can understand their duties and responsibilities and are able to show optimal performance